PROLIFIC USE OF MISLEADING ABBREVIATIONS BY HOSPICE HEALTHCARE PROFESSIONALS. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Bell, Sarah
Abstract : Background: The use of abbreviations is widespread amongst healthcare professionals, despite studies showing they can be misleading and lead to medical errors. For example, SCC is used for both spinal cord compression and squamous cell carcinoma. Junior hospice staff often come from a generalist background and may interpret abbreviations as having different meanings from those intended. Method: In order to evaluate the use of abbreviations at one hospice, a list of abbreviations were approved as being in standard use. The multidisciplinary notes from ten admissions were audited for non-approved abbreviations. Using the results of the initial audit, the approved list of abbreviations was revised and a limited duration hospice education programme was undertaken. A year later a further audit of abbreviation use in the notes was undertaken. Results: The initial audit found that 108 different, non-approved abbreviations were used on 735 occasions. Several abbreviations had more than one meaning, and the intended use and meaning varied significantly between individuals and disciplines. Disappointingly the re-audit showed only a 14% reduction in the use of non-approved abbreviations. This appeared to be particularly associated with junior doctors in short term posts. Conclusion: The use of potentially unsafe and misleading abbreviations is a prevalent and entrenched practice in hospice staff. Due to high junior doctor turnover, hospices need to develop rolling educations programmes to reach temporary as well as permanent staff.